Boganmeldelser - Heidi Mork Andersen; Ragnar Hauge; Lars Bo Langsted; Anette Storgaard; Hannu Takala; Hans Klette; Lars Rand Jensen; Knud Aage Frøbert; Alexander Carnera Ljungstrøm; Malene Frese-Madsen; Annalise Kongstad; Beth Grothe Nielsen (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews